Sports Orthopedics - Schneider S; Sauer J; Berrsche G; Löbel C; Schmitt H (Deutsche Zeitschrift für Sportmedizin)
Problem: Participating in competitive sport or training sessions despite being injured or in pain is very risky, but nevertheless very common. This behaviour, often referred to as playing hurt, is especially problematic among elite athletes due to the elevated risks of pain chronification, subsequent injuries and consecutive damages that may occur. The purpose of this study was to evaluate which internal and external determinants and context conditions play a role in the decision to play hurt. Methods: For this purpose we selected a nationwide collective of young basketball players from the highest national leagues. The German Adolescents and Childrens Health in Elite Basketball study (ACHE study), a quantitative survey conducted between April 2016 and June 2016, included a total sample size of n=182 elite basketball players between ages13 and 19 from 46 German teams.Results: Results show that playing while ill or in pain is common practice, even among young elite basketball players. Among all study participants, 39% indicated that they would play even if they did not feel well physically. The regression coefficients of multiple linear regression analyses revealed that groups that are particularly at risk for this behaviour include older adolescents, players who display over-conformity to a sports ethic, those who exhibit higher non-compliance with medical recommendations and players from sporting boarding or similar schools.Discussion: On the one hand, the results illustrate the important key role and thus the ethical responsibility that the athletes private and team doctors carry. On the other hand, there is an urgent need for a better communication and closer collaboration between the athlete and persons in charge (trainers, parents, doctors, physiotherapists and other caretakers). Our suggestion for improving the situation is an athletes conference similar to case conferences in the medical domain. KEY WORDS: Risk, Athletes, Adolescent, Injury, Pain